Essential oil composition and antioxidant activity of four Asteraceae species from Bosnia. Issue 5 (2nd September 2016) - Vidic, Danijela; Ćavar Zeljković, Sanja; Dizdar, Muamer; Maksimović, Milka
Abstract: Hydrodistilled volatile oils from Achillea millefolium L., Arnica montana L., Artemisia absinthium L., and Artemisia annua L. were analyzed by GC/MS. One hundred sixty-seven compounds were identified in all samples, ranging from 74.3% to 96.4% of the total oil. A high percentage of oxygenated monoterpenes is the main characteristic of A. millefolium and A. absinthium oils with camphor (19.2%) and isoascaridol (21.9%) as the major constituents, respectively. In contrast, the main component of A. annua oil was oxygenated sesquiterpene selina-3, 11-dien-6-α-ol (9.6%), while the chemical composition of A. montana oil was characterized by a high content of fatty acids with n -hexadecanoic acid (16.1%) as the main constituent. Antioxidant activity was tested using four different methods, DPPH, ABTS, Reducing power, and Phosphomolybdenum assay. The highest antioxidant activity had essential oil of A. montana using DPPH and Phosphomolibdenum assay, A. millefolium in ABTS method, while A. absinthium oil showed the best ability to reduce Fe ions.